Game theoretic perspective on threat detector deployment - Tan, Ye Sheng. (2013)
In the Battle of Okinawa during World War II, the Japanese used suicide bomber pilots or better known as “kamikaze pilots”, to inflict staggering damage to the American warships off the coast of Okinawa. 21 American warships were sunk and 66 other warships were badly damaged in a battle that left the American forces reeling from the effects of a new offensive sacrificial strategy which would develop into what is now known as the modern day suicide bomber[1]. Fast forward to the present day, terrorist militant groups like the Al-Qaeda and the Liberation Tigers of Tamil Eelam (LTTE) are the current advocates of the suicide bomber. These terrorists are willing to risk their own lives to deliver widespread damage to human lives and property, all for the sake of sending a strong message of their cause and beliefs.